Fornication as criminal act, Women's Vulnerability and the Stigma against Women's Movement - Mariana Amiruddin (Yayasan Jurnal Perempuan, 2018)
The paper explains how criminal code of zina (fornication) criminalized women victims of sexual violence. The data of Komnas Perempuan's Annual Records and the direct complaint from the victims can illustrate that women's personal relationships are particularly vulnerable to violence. The theories of feminism are used as an analytical tool of women's lives and their problems in the private sphere, including in terms of sexual relationships and love, whether married or not. This paper concludes with the challenge of the stigma of the feminist movement, as a movement considered to be opposed to morality and religion, and it is not just happen in Indonesia.